STUDY ON THE LOAD CONVERSION METHOD OF WHEEL-SIDE REDUCER CONSIDERING CITY LOAD CYCLE - NING Xin; ZHENG SongLin; XIE WenLong; FENG JinZhi (Jixie qiangdu)
The typical working condition of the vehicle comes from the city road cycle, the load distribution characteristics is obtained from the statistics and analysis on driving speed. With studying the effects of speed, acceleration, shock, gear and other factors on the load formation of the force transmission parts, the rotating mass scaling factor is adjusted. Take the wheel-side reducer for an instance, the conversion of the gear load is based on the parameters from vehicle and reducer, and the part load distribution corresponding to the vehicle speed is obtained. To explore the conversion method from the vehicle speed to the part load, and it provides the technological support for the lightweight design and the life analysis of parts in the reducer.